Two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material and its preparation method
Patent Information
- Application Number
- CN202310841670.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-07-11
AI Technical Summary
但是由于MXene的介电常数过高,可能导致阻抗不匹配使得吸波性能受到影响,如果引入磁性物质与MXene复合,磁损耗和介质损耗的协同效应、改善的阻抗匹配、增强的界面极化和传输路径可能使得复合物的电磁波吸收性能得到提升
[0010] In step two, the amounts of FeCl2·4H2O and NiCl2·6H2O added are 2.5 mmol and 7.5 mmol, respectively. The volume of the mixed solution of FeCl2·4H2O and NiCl2·6H2O is 80 mL, the mass of polyethylene glycol is 1 g, and the 50 wt% N2H4·H2O solution is 20 mL.
Smart Images

Figure CN116847644B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material and its preparation method. It belongs to the technical field of electromagnetic wave low-frequency absorbing material preparation. Background Technology
[0002] With the rapid development of information technology, electronic devices have greatly improved people's daily lives. Therefore, to address the increasingly serious electromagnetic pollution, researching easily prepared, sustainable, low-cost electromagnetic absorbing materials with superior absorption capabilities is of great significance. Electromagnetic wave absorbing materials can generate electromagnetic losses on incident electromagnetic waves, thereby converting the energy of electromagnetic waves into heat or other forms of energy. Currently, electromagnetic wave absorbing materials can be divided into two main categories: magnetic loss absorbing materials and dielectric loss absorbing materials. Magnetic loss materials generally include ferrites, metal oxides, and magnetic metal alloys; dielectric loss materials generally include graphene, carbonaceous materials, conductive polymers, two-dimensional sulfides, and MXene. In recent years, extensive research has been conducted on highly efficient electromagnetic wave absorbing materials. The requirements for absorbing materials are: strong reflection loss, wide effective absorption bandwidth, light weight, and thin matching thickness. According to impedance matching conditions, an ideal electromagnetic wave absorbing material has moderate dielectric loss and high magnetic loss. In addition, special structures can effectively enhance the attenuation of electromagnetic waves. For example, core-shell structures, flower-like structures, and multilayer structures can all cause electromagnetic waves to be reflected and scattered multiple times within the material, effectively dissipating more electromagnetic waves.
[0003] Previous research indicates that excellent electromagnetic wave absorption performance is due to the rational selection of components and the design of structures. Therefore, composite materials are an important design strategy for achieving high-efficiency electromagnetic absorption performance. MXene, as a novel element in two-dimensional materials, is also a general term for a class of transition metal carbides or nitrides. Because MXene possesses excellent electrical conductivity, good mechanical properties, a unique accordion shape, and metal-like characteristics, it has broad application prospects in energy storage, sensors, water treatment, electromagnetic shielding, and electromagnetic wave absorption. Studies have shown that combining magnetic or dielectric materials with MXene can effectively improve the electromagnetic wave absorption performance of MXene composites through structural design and interface construction. However, existing research methods can only attach magnetic materials to the surface of MXene, but cannot construct multilayer composite structures. MXene nanosheets were prepared by exfoliating the intermediate Al layer of a Ti3AlC2 precursor, allowing target ions to enter the interlayer spaces to form a multilayer composite structure. Different microstructures and compositions of the precursor will result in MXenes exhibiting different absorption capacities; the larger the sheet area and the higher the purity of the MXene, the better the EMW attenuation. However, due to the high dielectric constant of MXene, impedance mismatch may occur, which may affect the absorption performance. If magnetic materials are introduced to combine with MXene, the synergistic effect of magnetic loss and dielectric loss, improved impedance matching, enhanced interface polarization and transmission path may improve the electromagnetic wave absorption performance of the composite. Summary of the Invention
[0004] This invention proposes a two-dimensional FeNi3@MXene nanostructure electromagnetic wave low-frequency absorbing material and its preparation method. MXene nanosheets are prepared by stripping the intermediate Al layer of a Ti3AlC2 precursor, and then composited with FeNi3 alloy particles at room temperature to construct a multilayer composite electromagnetic wave absorbing material. The electromagnetic properties of this electromagnetic wave absorbing material can be controlled by the MXene doping ratio. This two-dimensional electromagnetic wave absorbing material exhibits a wide effective absorption bandwidth and excellent electromagnetic wave absorption performance at a low matching thickness.
[0005] The preparation method of this invention focuses on improving the synthesis method and electromagnetic wave absorption performance of the sample. The innovation of this experiment lies in the ability to construct a multilayer composite structure using simple experimental conditions, and the composite exhibits good electromagnetic wave absorption performance, providing an important research foundation for industrial applications.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows: A two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material contains multiple two-dimensional sheet-like structures, with FeNi3 alloy particles existing on the surface and between the sheet-like MXene layers.
[0007] A method for preparing a two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material includes the following steps: Step 1: Disperse LiF and Ti3AlC2 sequentially into a 9 mol / L hydrochloric acid solution and stir continuously at 35°C. After etching and stirring are completed, let the reaction solution stand and then use a dropper to collect the supernatant. Dilute with water until the pH is 7. Collect the product using a centrifuge and then freeze-dry it to collect the product. Step 2: Add FeCl2·4H2O and NiCl2·6H2O to deionized water, add the product from Step 1 to the above solution, sonicate, add polyethylene glycol, stir magnetically until completely dissolved, add NaOH solution, and finally add 50 wt% N2H4·H2O. Stir the mixed solution vigorously at room temperature for 5 h, and finally centrifuge and vacuum dry the product to collect the FeNi3@MXene product.
[0008] The mass of LiF is 2 g, the mass of Ti3AlC2 is 2 g, and the volume of 9 mol / L hydrochloric acid is 15 mL.
[0009] In step one, the etching temperature and time are 35 ℃ and 48 h, respectively, and the centrifuge speed in step one is 3500 rpm.
[0010] In step two, the amounts of FeCl2·4H2O and NiCl2·6H2O added are 2.5 mmol and 7.5 mmol, respectively. The volume of the mixed solution of FeCl2·4H2O and NiCl2·6H2O is 80 mL, the mass of polyethylene glycol is 1 g, and the 50 wt% N2H4·H2O solution is 20 mL.
[0011] In step two, the obtained FeNi3@MXene product is dried in a vacuum oven at 60 °C for 8 h.
[0012] This invention prepares MXene nanosheets by removing the intermediate Al layer of a Ti3AlC2 precursor, and then composites them with FeNi3 alloy particles at room temperature to construct a multilayer composite electromagnetic wave absorbing material. The electromagnetic properties of this material can be controlled by the composite ratio of MXene. This two-dimensional multilayer composite material has abundant interfaces, allowing incident electromagnetic waves to undergo multiple reflections and scattering between the nanosheets, resulting in more efficient dissipation of the incident electromagnetic waves. Simultaneously, the significant interfacial polarization effect attenuates more electromagnetic waves, contributing to improved dielectric loss. Furthermore, the composite structure contains encapsulated magnetic particles, which enhance the magnetic loss of the composite, thereby giving the composite material superior electromagnetic wave absorption performance.
[0013] The optimal hydrochloric acid concentration of 9 mol / L and the optimal exfoliation time of 48 h during the Ti3AlC2 exfoliation process resulted in the best electromagnetic wave absorption performance. The two-dimensional multilayer FeNi3@MXene nanomaterial of this invention exhibits excellent electromagnetic wave absorption performance and a wide effective absorption bandwidth, making it a relatively ideal electromagnetic wave absorbing material.
[0014] The morphology of this nanomaterial can be controlled by adjusting the MXene recombination ratio, thereby obtaining a two-dimensional multilayer FeNi3@MXene nanomaterial. The two-dimensional multilayer structure generates a large surface area, which enhances the multiple reflections and scattering of incident waves, providing more contact sites for electromagnetic waves. Therefore, this invention can achieve strong electromagnetic wave reflection loss and a wide effective absorption bandwidth.
[0015] This invention eliminates the need for highly toxic chemical reagents, employs a simple and controllable method, and is low-cost, making it suitable for large-scale industrial production. It can provide an important theoretical foundation for the research of ideal novel electromagnetic wave absorbing materials.
[0016] The experimental and theoretical results of this invention show that MXene nanosheets were prepared by removing the intermediate Al layer of the Ti3AlC2 precursor, and then the two-dimensional multilayer structure obtained by compositing it with FeNi3 alloy particles at room temperature can exhibit good electromagnetic wave absorption performance. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 The XRD patterns of MXene, FeNi3, FeNi3@MXene-20, FeNi3@MXene-60 and FeNi3@MXene-100 obtained in this invention are shown. Figure 2 This is a SEM image of MXene from the present invention; Figure 3 This is a SEM image of FeNi3 from the present invention; Figure 4 This is a SEM image of FeNi3@MXene-20 from the present invention; Figure 5 This is a SEM image of FeNi3@MXene-60 from the present invention; Figure 6 This is a SEM image of FeNi3@MXene-100 from the present invention; Figure 7 This is a reflection loss diagram of FeNi3@MXene-20 of the present invention; Figure 8 This is a reflection loss diagram of FeNi3@MXene-60 of the present invention; Figure 9 This is a reflection loss diagram of FeNi3@MXene-100 of the present invention; Figure 10 This is a graph showing the relationship between the magnetic field strength and magnetization of FeNi3 and FeNi3@MXene in this invention. Detailed Implementation
[0019] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0020] A two-dimensional FeNi3@MXene nanostructure electromagnetic wave low-frequency absorbing material, wherein the electromagnetic wave absorbing material contains multiple two-dimensional sheet-like structures, and FeNi3 alloy particles exist on the surface and between the sheet-like MXene layers.
[0021] A method for preparing a two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material includes the following steps: Step 1: Disperse LiF and Ti3AlC2 sequentially into a 9 mol / L hydrochloric acid solution and stir continuously at 35°C. After etching and stirring are completed, let the reaction solution stand and then use a dropper to collect the supernatant. Dilute with water until the pH is 7. Collect the product using a centrifuge and then freeze-dry it to collect the product. Step two: Add a certain amount of FeCl2·4H2O and NiCl2·6H2O to deionized water. Add the product from step one to the above solution, sonicate for a certain time, then add polyethylene glycol and stir magnetically until completely dissolved. Add NaOH solution, and finally add 50 wt% N2H4·H2O. Stir the mixture vigorously at room temperature for 5 hours. Finally, centrifuge and vacuum dry the product to collect the FeNi3@MXene product. Example
[0022] A method for preparing a two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material includes the following steps: Step 1: 2 g LiF and 2 g Ti3AlC2 were successively dispersed in a 9 mol / L hydrochloric acid solution and stirred continuously at 35 °C for 48 h. After etching and stirring were completed, the reaction solution was allowed to stand for a period of time, and the supernatant was aspirated with a dropper and diluted with water until the pH reached 7. The product was collected using a centrifuge at 3500 rpm. Finally, the product MXene was obtained by lyophilization.
[0023] Step 2: Add 2.5 mmol FeCl2·4H2O and 7.5 mmol NiCl2·6H2O to 80 mL of deionized water. Add 20 mg of MXene, the product from Step 1, to the above solution. Sonicate for a certain time, then add 1 g of polyethylene glycol (PEG) and stir magnetically until completely dissolved. Add 10 mL of 5 mol / L NaOH solution, and finally add 20 mL of N2H4·H2O (50 wt%). Stir the mixture vigorously at room temperature for 5 h. Centrifuge the product and vacuum dry for 8 h. The collected sample is designated FeNi3@MXene-20. Example
[0024] A method for preparing a two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material includes the following steps: Step 1: 2 g LiF and 2 g Ti3AlC2 were successively dispersed in a 9 mol / L hydrochloric acid solution and stirred continuously at 35 °C for 48 h. After etching and stirring were completed, the reaction solution was allowed to stand for a period of time, and the supernatant was aspirated with a dropper and diluted with water until the pH reached 7. The product was collected using a centrifuge at 3500 rpm. Finally, the product MXene was obtained by lyophilization.
[0025] Step 2: Add 2.5 mmol FeCl2·4H2O and 7.5 mmol NiCl2·6H2O to 80 mL of deionized water. Add 60 mg of MXene, the product from Step 1, to the above solution. Sonicate for a certain time, then add 1 g of polyethylene glycol (PEG) and stir magnetically until completely dissolved. Add 10 mL of 5 mol / L NaOH solution, and finally add 20 mL of N2H4·H2O (50 wt%). Stir the mixture vigorously at room temperature for 5 h. Centrifuge the product and vacuum dry for 8 h. The collected sample is designated FeNi3@MXene-60. Example
[0026] A method for preparing a two-dimensional FeNi3@MXene nanostructured electromagnetic wave low-frequency absorbing material includes the following steps: Step 1: 2 g LiF and 2 g Ti3AlC2 were successively dispersed in a 9 mol / L hydrochloric acid solution and stirred continuously at 35 °C for 48 h. After etching and stirring were completed, the reaction solution was allowed to stand for a period of time, and the supernatant was aspirated with a dropper and diluted with water until the pH reached 7. The product was collected using a centrifuge at 3500 rpm. Finally, the product MXene was obtained by lyophilization.
[0027] Step 2: Add 2.5 mmol FeCl2·4H2O and 7.5 mmol NiCl2·6H2O to 80 mL of deionized water. Add 60 mg of MXene, the product from Step 1, to the above solution. Sonicate for a certain time, then add 1 g of polyethylene glycol (PEG) and stir magnetically until completely dissolved. Add 10 mL of 5 mol / L NaOH solution, and finally add 20 mL of N2H4·H2O (50 wt%). Stir the mixture vigorously at room temperature for 5 h. Centrifuge the product and vacuum dry for 8 h. The collected sample is designated FeNi3@MXene-100.
[0028] Figure 1 XRD patterns for MXene, FeNi3, FeNi3@MXene-20, FeNi3@MXene-60, and FeNi3@MXene-100 are shown. The standard patterns corresponding to all diffraction peaks are as follows: MXene and FeNi3 (JCPDS 88-1715). From Figure 1 In the XRD pattern, the diffraction peaks at 2θ = 5.700°, 34.842°, and 64.659° correspond to the (002), (0010), and (110) crystal planes of MXene. The diffraction peaks at 2θ = 44.119°, 51.470°, and 75.842° correspond to the (111), (200), and (220) crystal planes of FeNi3. The composite material FeNi3@MXene exhibits predominantly MXene and FeNi3 diffraction peaks. Figure 1 The high intensity and sharpness of the diffraction peaks at 2θ = 44.119°, 51.470°, and 75.842° indicate that FeNi3 has good crystallinity. The smaller diffraction peaks at 2θ = 5.700°, 34.842°, and 64.659° are due to the relatively small mass of MXene added to the composite. Furthermore, it can be observed that the intensity of the diffraction peak at 2θ = 5.700° gradually increases with increasing MXene doping concentration. The XRD pattern confirms the successful synthesis of the FeNi3@MXene composite material.
[0029] Figure 2 , 3 Images 4, 5, and 6 are SEM images of MXene, FeNi3, FeNi3@MXene-20, FeNi3@MXene-60, and FeNi3@MXene-100, respectively. As can be seen from the images, the more MXene is added, the more obvious the lamellar structure of the FeNi3@MXene composite becomes.
[0030] Figure 7 The reflection loss diagram for FeNi3@MXene-20 is shown below. Figure 6 It can be seen that FeNi3@MXene-20 exhibits good microwave absorption performance. When the thickness is 2.66 mm and the frequency is 6.52 GHz, the maximum reflection loss can reach -65.98 dB; when the thickness is 1.36 mm, the optimal effective bandwidth is 4.64 GHz.
[0031] Figure 8 The reflection loss diagram for FeNi3@MXene-60 is shown below. Figure 7 It can be seen that FeNi3@MXene-60 exhibits good microwave absorption performance. When the matching thickness is 3.63 mm and the frequency is 3.92 GHz, the maximum reflection loss can reach -48.19 dB; when the thickness is 1.25 mm, the optimal effective bandwidth is 4.28 GHz.
[0032] Figure 9 The reflection loss diagram for FeNi3@MXene-100 is shown below. Figure 8 It can be seen that FeNi3@MXene-100 exhibits excellent microwave absorption performance. When the thickness is 1.50 mm and the frequency is 14.60 GHz, the maximum reflection loss can reach -63.93 dB; when the thickness is 1.45 mm, the optimal effective bandwidth is 5.12 GHz.
[0033] Figure 10 The graph shows the relationship between the magnetic field strength and magnetization of FeNi3 and FeNi3@MXene. Figure 9 The saturation magnetizations of FeNi3, FeNi3@MXene-20, FeNi3@MXene-60 and FeNi3@MXene-100 were obtained as 90.66 emu / g, 85.57 emu / g, 79.12 emu / g and 74.14 emu / g, respectively.
[0034] This invention prepares MXene nanosheets by stripping the intermediate Al layer of a Ti3AlC2 precursor, and then constructs a multilayer composite electromagnetic wave absorbing material by combining it with FeNi3 alloy particles at room temperature. In the FeNi3@MXene composite material, the introduction of FeNi3 alloy particles significantly improves the magnetic permeability, thereby increasing the magnetic loss. Simultaneously, the presence of multilayered MXene ensures a high dielectric constant, leading to interfacial polarization and multilayer scattering of electromagnetic waves, further enhancing the dielectric loss. Due to the synergistic effect of dielectric and magnetic losses, the impedance matching of the composite material is further optimized. Figure 7 , Figure 8 and Figure 9 It can be seen that with the addition of MXene, the low-frequency electromagnetic properties of the composite material are better. The FeNi3@MXene-60 sample has a reflection loss intensity of -48.19 dB at a frequency of 3.92 GHz when the matching thickness is 3.63 mm, and has an effective absorption bandwidth of 4.28 GHz at a matching thickness of 1.25 mm.
[0035] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional FeNi3@MXene nanostructure electromagnetic wave low-frequency absorbing material, characterized in that: The electromagnetic wave low-frequency absorbing material contains multiple two-dimensional sheet-like structures, with FeNi3 alloy particles present on the surface and between the sheet-like MXene layers, and includes the following steps: Step 1: Disperse LiF and Ti3AlC2 sequentially into a 9 mol / L hydrochloric acid solution and stir continuously at 35°C. After etching and stirring are completed, let the reaction solution stand and then use a dropper to collect the supernatant. Dilute with water until the pH is 7. Collect the product using a centrifuge and then freeze-dry it to collect the product. Step 2: Add FeCl2·4H2O and NiCl2·6H2O to deionized water, add the product from Step 1 to the above solution, sonicate, then add polyethylene glycol, stir magnetically until completely dissolved, then add NaOH solution, and finally add 50wt% N2H4·H2O. Stir the mixed solution vigorously at room temperature for 5 h, then centrifuge and vacuum dry the product to collect the FeNi3@MXene product.
2. The preparation method of a two-dimensional FeNi3@MXene nanostructure electromagnetic wave low-frequency absorbing material according to claim 1, characterized in that: The mass of LiF is 2 g, the mass of Ti3AlC2 is 2 g, and the volume of 9 mol / L hydrochloric acid is 15 mL.
3. The preparation method of a two-dimensional FeNi3@MXene nanostructure electromagnetic wave low-frequency absorbing material according to claim 1, characterized in that: In step one, the etching temperature and time are 35 ℃ and 48 h, respectively, and the centrifuge speed in step one is 3500 rpm.
4. The preparation method of a two-dimensional FeNi3@MXene nanostructure electromagnetic wave low-frequency absorbing material according to claim 1, characterized in that: In step two, the amounts of FeCl2·4H2O and NiCl2·6H2O added are 2.5 mmol and 7.5 mmol, respectively. The volume of the mixed solution of FeCl2·4H2O and NiCl2·6H2O is 80 mL, the mass of polyethylene glycol is 1 g, and the 50 wt% N2H4·H2O solution is 20 mL.
5. The preparation method of a two-dimensional FeNi3@MXene nanostructure electromagnetic wave low-frequency absorbing material according to claim 1, characterized in that: In step two, the obtained FeNi3@MXene product is dried in a vacuum oven at 60 °C for 8 h.
Citation Information
Patent Citations
Composite wave-absorbing material with rare earth element-doped magnetic particles loaded on layered MXene
CN113260242A